Menguak Paradoks Activity-Based Management: Optimalisasi Biaya atau Sekadar Ilusi Kontrol? - Nazari, Esa Cahyani; Catherine; Nur Aisyah, Putri; Yusnaini (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
Activity-Based Management (ABM) is a strategic approach used to optimize costs by identifying value-added activities and eliminating non-essential activities. This study aims to analyze the effectiveness of ABM in improving cost efficiency and uncover paradoxes that may arise in its application, such as the illusion of control in corporate financial management. This study uses a qualitative approach with the Systematic Literature Review (SLR) method, reviewing 40 relevant articles from national and international journals. The results showed that 37 studies supported the effectiveness of ABM in improving cost efficiency through the elimination of non-value-added activities, resulting in increased profitability. Examples of implementation in the hospitality and manufacturing sectors showed significant reductions in operating costs. However, three other studies highlighted challenges in implementing ABM, such as system complexity, high investment costs, and internal resistance that can hinder its effectiveness. Thus, the success of ABM is highly dependent on the organization's readiness to face implementation challenges, technological readiness, and managerial support. Without a well-thought-out strategy, ABM risks becoming just an illusion of control that has no real impact on the company's cost efficiency. Therefore, this research provides insight into the optimal strategy for implementing ABM to improve business competitiveness in a sustainable manner.